1997
DOI: 10.2466/pms.1997.84.3c.1223
|View full text |Cite
|
Sign up to set email alerts
|

Psychology of Computer Use: XLVI. Age-Related Differences in the Mapping of Auditory Icons to Visual Icons in Computer Interfaces for Children

Abstract: An investigation was conducted to characterize how children ages 6 through 9 identify auditory icons present in educational software. 24 subjects were require to map auditory icons to visual icons, both present in a computer interface. The interface used in the experiment was constructed with Visual Basic and involved 40 auditory icons, 40 corresponding visual icons, and 66 extraneous visual icons. It was hypothesized that older children would be better able to map the auditory icons to visual icons due to mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Concerning the sounds, the human and animal voices were liked much better than traffic noise, which agree with the results from previous research (Shimai et al, 1993). Jacko and Rosenthal's (1997) study showed that some traffic sounds might be difficult to recognize for children. In this study, recognition was never tested, because in TRAFFIC JAM, all the sounds are closely connected with the corresponding pictures.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Concerning the sounds, the human and animal voices were liked much better than traffic noise, which agree with the results from previous research (Shimai et al, 1993). Jacko and Rosenthal's (1997) study showed that some traffic sounds might be difficult to recognize for children. In this study, recognition was never tested, because in TRAFFIC JAM, all the sounds are closely connected with the corresponding pictures.…”
Section: Discussionsupporting
confidence: 94%
“…From their studies of children's ability to identify auditory icons in computer interfaces, Jacko and Rosenthal (1997) concluded that most 7-and 9-year-olds could identify correctly animal sounds such as birds chirping and dogs barking. A car ignition was also identified fairly easily, whereas cars passing seemed to be more difficult to recognize.…”
Section: Illustrating Environmental Impactmentioning
confidence: 98%
“…In searching the literature, there are many examples of how auditory perception takes on this environment-orientated role. For example, from a young age we are able to correctly match everyday sounds to their everyday seen objects (see [25]). In adult listeners, reports and categorizations become more detailed still, with the materials, actions and the tasks that sounds are involved in all being recognized and reported [26][27][28].…”
Section: Sounds In the Worldmentioning
confidence: 99%
“…Experimental research has shown that even young children find it relatively easy to match sounds to an appropriate event in just one trial (Jacko & Rosenthal , 1997). By contrast, the acoustic properties of the sound in a symbolic mapping bear no resemblance to the event it signals-such an association must be learned through contiguous exposure.…”
Section: Learning Sound-event Relationsmentioning
confidence: 99%